Proposi dan karakteristik mahasiswa penderita nyeri punggung di Fakultas Kedokteran Universitas Udayana Tahun 2018 - Feliani Sanjaya; Yuliana Yuliana; Muliani Muliani (Bali Anatomy Journal, 2019)
Back pain is one of the most common illness in society and it is able to decrease the sufferer’s mobility also productivity. Aim of this study is to find out the proportion and the characteristic of students who suffer from back pain in Medical Faculty Udayana University, academic year of 2015-2017. This study was conducted with descriptive cross-sectional design. The number of samples was 302 people taken by consecutive sampling method and respondents were measured their waist circumference and asked to fill out the questionnaire. There are two types of questionnaire used to be filled out by the respondents depending on the accessibility of the respondents, they are paper questionnaire and online questionnaire. The data obtained was managed with SPSS 16.0 and presented in table form. The results of this study were the proportion of back pain sufferers among Medical Faculty students as much as 34.8%, which was dominated by lower back pain. There were 8 variables of characteristics of people with back pain, including gender, body mass index, central obesity, physical activity, weight of backpack, history of vertebra injury, working position, and sitting position. This study can be concluded that in the student population of the Faculty of Medicine, Udayana University, sufferers of back pain are dominated by women, underweight, central obesity sufferers, daily exercise frequency, excessive backpack load, history of spinal cord injury, incorrect work position, and incorrect sitting position.